Experiences of Forming the Social Image of a Modern Leader in Uzbekistan - Yuldashev B. E. (Researchparks Publishing, 2022)
In this article, the experiences of forming a modern leader, in order to improve his social image, the analysis and generalization of the accumulated experiences in this regard in the following years, the determination of future tasks, and the determination of activities related to their implementation are justified. It has been scientifically analyzed that without identifying these tasks and ensuring their systematic solution, it is impossible to decide on a modern leader who will serve the interests of the country and the Motherland.